Assorted optical solitons of the (1+1)- and (2+1)-dimensional Chiral nonlinear Schrödinger equations using modified extended tanh-function technique - Luo, Jiaming; Manafian, Jalil; Eslami, Baharak; Mahmoud, K. H.; Sharma, Rohit; Kumari, Neha; Alsubaie, A. SA (Scientific reports, 2024)
In this research article, the (1+1)- and (2+1)-dimensional Chiral nonlinear Schrödinger equations (CNLSEs) are studied, which play an important role in the development of quantum mechanics, particularly in the field of quantum Hall effect. Our primary goal is to obtain the analytical solutions utilizing novel methodology, particularly the modified extended tanh-function technique. We concentrate on the search to solitary wave solutions inside the (1+1)- and (2+1)-dimensional CNLSEs, which are relevant in domains such as optics, electro-magnetic wave propagation, plasma physics, optics and quantum mechanics. Our objective is to increase knowledge of this equation and give insight into the behavior of solitary waves by employing a novel mathematical technique. This will be accomplished by displaying our findings in 2D and 3D graphics. We believe that our results would pave a way for future research generating optical memories based on the nonlinear solitons.